Studi Pertumbuhan dan Produksi Dua Varietas Bawang Merah (Allium ascalonicum L.) Terhadap Waktu Penyiangan Gulma - Josua Bonar Pohan; lisa Mawarni; Toga Simanungkalit (Universitas Sumatera Utara, 2015)
The time of weeding between weed and shallots can influence the decreasing of growth and productions. The uncorrect time of weeding can make looses. This research had been conducted at Simalingkar residences in Juny until September 2014 using factorial randomized block design with two factor, The first factor was 7 times of weeding K1: clean of weed for 0-3 weeks, K2 : clean of weed for 0-5 weeks, K3: clean of weed for 0-7 weeks, K4: without of weed for 0-3 weeks, K5: without of weed for 0-5 week, K6: without of weed for 0-7 weeks, and K7: clean of weed until harvest and two factor as varieties namely V1 Bima and V2 Medan. The parameters were plant height per tuber, number of leaves per tuber, numbers of tillersper hill, fresh tuber production per plot, dried tuber production per plot, kind of weed .The result showed that the time of weeding significantly decrease plant height of 3 weeks after plants (wap) and number of leaves at 5 wap .Keywords: the time of weeding, varieties, growth and yields, shallots